Preparation of Very Thin Zinc Oxide Films by Liquid Deposition Process: Review of Key Processing Parameters - Khiari, Mouna; Gilliot, Mickaël; Lejeune, Michaël; Lazar, Florica; Hadjadj, Aomar (Coatings, 2022)
We used sol-gel and spin-coating in the original configuration of a liquid deposition process to synthesize particularly thin ZnO films (<100 nm) with nano-granular morphology, high grain orientation and variable optical properties. The concentration of the zinc salt, the concentration of the chelating agent, the nature of the solvent and the substrate material have been identified as key parameters that determine the microstructure of the deposited layer and thus its final properties. The thorough and practical examination of the effects of the synthesis parameters evidenced a three-step growth mechanism for these ZnO thin films: (i) a reaction of precursors, (ii) a formation of nuclei, and (iii) a coalescence of nanoparticles under thermal annealing. The growth of these very thin films is thus conditioned by the interaction between the liquid phase and the substrate especially during the initial steps of the spin coating process. Such thin ZnO films with such nano-granular morphology may be of great interest in various applications, especially those requiring a large active surface area.
Number: 1
Keywords: ZnO; chelating agent; deposition; ellipsometry; microstructure; morphology; sol-gel; solvent; spin-coating; substrate; thin film